Feeding practices and early childhood caries among children with primary dentition - Sundas, Sunanda; Sah, Barun Kumar; Dhakal, Neha; Rai, Amita; Joshi, Neera (Journal of Kathmandu Medical College, 2021)
Background: Early childhood caries (ECC) is major oral health problem of young children. Risk factors for ECC are poor oral hygiene and feeding practices. Prevalence and severity of ECC is increasing with change in lifestyle and diet pattern in developing countries.Objectives: To assess the association between feeding practices and severity of early childhood caries in preschool children.Methods: An analytical cross-sectional study was conducted with convenient sample of 96 children up to six years age in Peoples Dental College from July to December 2020. Clinical examination included the recording of dental caries (dmft) using WHO criteria. The self-validated questionnaire consisting seven questions about feeding practices was asked to mothers. The Chi-square test was performed to determine association between severity of ECC and feeding pattern.Results: Mean dmft was 6.77 ± 5.91. Prevalence of severe-ECC (S-ECC) was highest in youngest age group. Caries experience was similar in breast fed, bottle fed, and mixed. There was no significant difference in non-severe ECC and ECC in relation to duration of breast or bottle feeding but frequency of night feeding was associated with S-ECC. Children given ready-made infant formula solid food had more S-ECC (13, 92%) compared to non-severe ECC (1, 7.1%) which was statistically significant. Children given homemade gram flour food were noted to have less of S-ECC (5, 27.5%) than nonsevere ECC (13, 72.5%) which was statistically significant.Conclusion: Present study revealed that multiple night feeding and weaning with readymade food are significant factors for S-ECC.